PENGUKURAN KINERJA USAHA KECIL MENENGAH MENURUT FAKTOR KOMPETENSI SUMBER DAYA MANUSIA - KARMILATI KARMILATI; RR. NIKEN PURBASARI (Jurnal Bisnis dan Akuntansi, 2012)
The background of this research is the idea that competition for the future is competition of opportunity share rather than market share. The competition for the future is not product versus product, but the company versus company. The Capable Company needed to access the new opportunity arena, like market, resources, technology, changing processes, meaning that competition, is as much a battle between competing and often overlapping coalitions and between individual firms. The capable company is a company with high performance. The company should be setting best corporate strategy to get high performance. Corporate strategy is primarily about the choice of direction based on its competencies for the firm as a whole, whether the firm is a small, or a single product company. The competencies needed to get high performance and can be accessed the new opportunity. The limited question of this research is there any influence between Knowledge and UKM performance, Skill and UKM performance, Attitudes and UKM performance. The design of this research applies survey method with employer of small and middle business company (UKM) in Pulo Gadung Jakarta. The method of this research is using technical regres-sion. The result showed that there is positif influence between Knowledge and UKM Performance, Skill and UKM Performance, Skill and UKM Performance, Attitude and UKM Performance.